Childfree di Indonesia: Analisis Yuridis atas Pertentangan Hak Reproduksi dan Kewajiban Ḥifẓ al-Nasl - Kaila Hana Ramadhani; Habib Siddiq Siregar; Alila Natasya Berelaka; Mutia Nabilla Balqist Nasution; Nayla Kirana Gading Batubara (Tabayyun : Journal Of Islamic Studies, 2026)
The childfree phenomenon, defined as a conscious choice by individuals or couples not to have children, has increasingly become a social discourse in Indonesia. This lifestyle raises complex legal and ethical questions, particularly regarding the balance between individual reproductive rights and the Islamic obligation of ḥifẓ al-nasl (preservation of lineage), a key principle within maqāṣid al-sharī‘ah. This study employs a normative-juridical approach, combining classical Islamic legal sources, contemporary scholarship, and human rights instruments, to examine whether childfree decisions can be reconciled with Islamic legal principles. The findings indicate that temporary or contextually justified childfree choices may align with maqāṣid principles, particularly when based on health, psychological, or socio-economic considerations. However, permanent childfree choices driven by individualistic or hedonistic motives may conflict with the preservation of lineage and family continuity. This research contributes to bridging the discourse between Islamic law and contemporary reproductive autonomy, emphasizing the need for adaptive legal interpretations that respect both individual rights and communal obligations.